Identification of Lost Space in Madiun City: Characteristics and Variations - Alimudin, Dai; Roychansyah, Muhammad Sani (Riwayat: Educational Journal of History and Humanities, 2025)
This study identifies and analyzes lost spaces in Madiun, focusing on public green open spaces (RTHP). Lost spaces refer to areas that fail to function optimally, undermining the city's social, ecological, and aesthetic activities. A descriptive qualitative approach was used to evaluate 43 RTHP locations across three districts in Madiun: Taman, Manguharjo, and Kartoharjo. Survey and scoring methods were applied to assess accessibility, activity history, facilities, and space categories at each location. The results identified seven locations as lost spaces, including Bosbow Area, Janoko Street Park, and Reksogati Football Field, with characteristics such as abandoned military sites, neglected parks, and poorly maintained public squares. The key factors contributing to these conditions are low levels of accessibility, visibility, and imageability. This study provides recommendations for revitalization through infrastructure improvements, preservation of historical value, and development of community facilities to create more sustainable and inclusive open spaces. These findings serve as a critical foundation for urban planning that prioritizes community needs and environmental sustainability.